PROPOSED COMPETITIVE STRATEGIES OF CONTRACTOR COMPANIES - Hishan Shanker Sanil; Irfan Nurdiansyah; Erwan Prastiawan (FEBI UIN Sunan Gunung Djati Bandung, 2022)
The construction industry is one such sector that is quite promising regarding governmental support in this area. The needs of the Indonesian state regarding development are one of the key factors for improving this sector. The construction industry consists of several groups; the small groups are often the target of competitive businesses within the industry, which often negatively impacts their expansion and growth. This makes the government support for small construction service providers a crucial stage in enabling them to compete with larger companies, one of which is CV. IWK. This company currently relies upon and utilizes the owner's extensive experience within the sector and its overall quality of work. However, the company has yet to focus on its marketing and workforce to capitalize on its potential growth fully. Thereby, it tends to find it difficult to meet project targets and obligations. The company needs to maximize its strengths and further its current position in the sector by employing an appropriate strategy to implement continued market penetration via internal development. This is reinforced by the QSPM analysis results, which show that this strategy is the best choice for the company moving forward in such a competitive market. To succeed, the company's main focus is to delegate labor to the marketing function.